The Utilization Of Whatsapp Media As A Student's Digital Literation Media In Distance Learning In SMA Private Santo Thomas 2 Medan - Rikson Parsaoran Manurung (Indonesian Journal of Education and Mathematical Science, 2020)
The Utilization Of Whatsapp Media As A Student's Digital Literation Media In Distance Learning In SMA Private  Santo Thomas 2 Medan